EFFICACY OF MATRABASTI ON KASHTARTAVA (PRIMARY DYSMENORRHOEA) - Jangale, Jyoti (International Journal of Ayurveda and Pharma Research, 2018)
In today’s lifestyle woman’s status is expected to reach new horizons both socially and physically but some of the physiological things trouble the lady to make her slow down the race, by disturbing the normal menstruation, which is the function of Apana vayu. One of such problem is ‘Kashtartava’ (Dysmenorrhoea) i.e. painful menstruation.In Ayurvedic texts, though various conditions are described in which menstruation occurs with pain but Kashtartava is not mentioned specifically. It is a symptom of various Yonivyapadas specially Udavarta, Vatala, Sannipatika etc. The genital tract of women does not get affected without Vata, Hence one should pacify it first and then treat the other Doshas. For Vata dosha basti chikitsa is very important.Matrabasti is used by someone who emaciated by overwork or too much exercise, too much heavy lifting, walking too long of a distance, too much sexual activity or someone with Vata disorders. One of the effects of Matrabasti is “Vatarognut”, Hence Matrabasti may be effective on Kashtartava (Dysmenorrhoea).From above study, it can be concluded that due to Basti chikitsa vitiated Vata dosha gets mitigated and hence all the symptoms diminish and it has been observed that Til taila Matra Basti is very effective in subjects of Kashtartava (Primary Dysmenorrhoea).